La territorializzazione dell’esclusione sociale e della violenza a Rio de Janeiro - Saborío, Sebastián (2016)
Through a review of existing literature about Rio de Janeiro’s favelas, the author demonstrates how territorialisation of social exclusion plays a decisive role in increase and delimitate violence within more disadvantaged urban areas. Furthermore, this contribute shows how poverty’s criminalisation carries out a legitimating function towards social inequality and police violence against socially excluded categories. Key words: territorialisation, social exclusion, violence, gangs, police, favelas. Parole chiave: territorializzazione, esclusione sociale, violenza, gang, polizia, favelas.